An endogenous bornavirus‐like nucleoprotein in miniopterid bats retains the RNA‐binding properties of the original viral protein - Mukai, Yahiro; Horie, Masayuki; Kojima, Shohei; Kawasaki, Junna; Maeda, Ken; Tomonaga, Keizo (FEBS letters, 2022)
Endogenous bornavirus‐like nucleoprotein elements (EBLNs) are sequences derived from bornaviral N genes in vertebrate genomes. Some EBLNs have been suggested to encode functional proteins in host cells; however, little is known about their evolution and functional relationship to the viral genes from which EBLNs originate. Here, we predicted functionality of EBLNs based on the properties of N as an RNA‐binding protein. We showed an EBLN in miniopterid bats (miEBLN‐1) has evolved under purifying selection and encodes an RNA‐binding protein (miEBLN‐1p) with biochemical properties similar to bornaviral N. Furthermore, we revealed miEBLN‐1p interacts with host RNA‐binding proteins, such as MOV10. These data suggest that miEBLN‐1p has been exapted as an RNA‐binding protein with similar properties to exogenous bornaviral N in miniopterid bats. This study shows that miniopterid bats have a gene derived from the N gene of an ancient bornavirus, named miEBLN‐1, which has evolved under purifying selection. Furthermore, miEBLN‐1 encodes an RNA‐binding protein that interacts with several cellular RNA‐binding proteins, such as MOV10, with biochemical properties similar to bornaviral N proteins. Altogether, we provide strong evidence for the exaptation of miEBLN‐1.